Advances in Wheat Genetics: From Genome to Field 2015
DOI: 10.1007/978-4-431-55675-6_33
|View full text |Cite
|
Sign up to set email alerts
|

Complex G × E Interactions and QTL Clusters Govern End-Use Quality Traits in Hexaploid Wheat

Abstract: Evaluation of wheat end-use quality in terms of loaf volume (LV) requires enormous time and labor inputs. Hence, many studies have attempted to use grain, fl our and dough properties to predict LV. Many quantitative trait loci (QTL) underlying these traits have also been identifi ed to facilitate breeding. However, correlations between such predictive tests and LV as well as their QTLs could be infl uenced by the environment. In this chapter, we review recent literature on the correlations and G × E interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
1
0
1
Order By: Relevance
“…These results were in agreement with those of Patil et al (2009), who also reported a wide heritability range of 0.17 to 0.96 for mixograph-relative parameters. In contrast to our results, Tsilo et al (2011) and Prashant et al (2015) found high broad-sense heritability for most of the end-use quality traits in wheat. Similarly, the current study, Echeverry-Solarte et al (2015) reported very high broad-sense heritability for flour extraction and MMLPT.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results were in agreement with those of Patil et al (2009), who also reported a wide heritability range of 0.17 to 0.96 for mixograph-relative parameters. In contrast to our results, Tsilo et al (2011) and Prashant et al (2015) found high broad-sense heritability for most of the end-use quality traits in wheat. Similarly, the current study, Echeverry-Solarte et al (2015) reported very high broad-sense heritability for flour extraction and MMLPT.…”
Section: Discussioncontrasting
confidence: 99%
“…The genetic and Pearson correlation analyses revealed most of the end-use quality traits were associated with each other. Several previous studies have also reported similar results (Patil et al 2009; Tsilo et al 2011; Prashant et al (2015); Echeverry-Solarte et al 2015). Our results showed differences between genetic and phenotypic correlation coefficients for end-use quality traits.…”
Section: Discussionsupporting
confidence: 80%